2021
DOI: 10.1200/jco.2021.39.15_suppl.4128
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicenter phase Ib/II study of neoadjuvant chemoradiation therapy (CRT) alone or in combination with pembrolizumab in patients with resectable or borderline resectable pancreatic cancer.

Abstract: 4128 Background: Pancreatic cancer (PC) is a challenging target for immunotherapy due to suppressive immune-microenvironment. Neoadjuvant chemoradiation (CRT) can increase the presence of tumor-infiltrating lymphocytes (TILs). We hypothesized that the combination of CRT and pembrolizumab can lead to further increase in TILs and their activation. Methods: Patients with resectable or borderline resectable PC were randomized 2:1 to the investigational treatment (Arm A) of pembrolizumab 200mg IV every 3 weeks con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…132 Moreover, in a randomized phase Ib/II trial, the addition of the anti-PD-1 antibody pembrolizumab to neoadjuvant capecitabine-based chemoradiation did not lead to improved outcomes for patients with resectable or borderline resectable PDAC. 133 Indeed, recent data suggest other immune checkpoints, such as TIGIT, 134 are important drivers of immune surveillance evasion in PDAC, and studies are ongoing to evaluate the efficacy of inhibitors of other immune checkpoints in the advanced disease setting.…”
Section: Immunotherapy For Localized Pdacmentioning
confidence: 99%
“…132 Moreover, in a randomized phase Ib/II trial, the addition of the anti-PD-1 antibody pembrolizumab to neoadjuvant capecitabine-based chemoradiation did not lead to improved outcomes for patients with resectable or borderline resectable PDAC. 133 Indeed, recent data suggest other immune checkpoints, such as TIGIT, 134 are important drivers of immune surveillance evasion in PDAC, and studies are ongoing to evaluate the efficacy of inhibitors of other immune checkpoints in the advanced disease setting.…”
Section: Immunotherapy For Localized Pdacmentioning
confidence: 99%
“…The targets for these agents include CTLA-4, PD-1, and PD-L1, which are involved in many malignant tumors [ 43 ]. Based on phase Ib/II (NCT02305186), the combinational treatment consisting of Pembrolizumab, a PD-1 inhibitor (IV administration of 200 mg, every 3 weeks), radiotherapy, and capecitabine, a cytotoxic agent (oral administration of 825 mg/m 2 1×2 per day) proved beneficial as a neoadjuvant therapeutic strategy with a notable increase of overall survival (OS) compared to radiation alone [ 44 ]. For resectable PDAC, there is an ongoing phase II trial (NCT03727880) assessing the combination of Pembrolizumab with defactinib (a focal adhesion kinase inhibitor) or Pembrolizumab as an adjuvant or neoadjuvant immunotherapeutic strategy for resectable tumors [ 45 ].…”
Section: Immunotherapy In Pancreatic Adenocarcinomamentioning
confidence: 99%
“…In phase Ib/II trial (NCT02305186), Rahma et al reported that pembrolizumab, an immune checkpoint inhibitor (anti-PD-1 IgG4 antibody), in combination with capecitabine and radiation as neoadjuvant regimen resulted in increased median recurrence free survival (RFS), 18.2 vs 14.1 months (p = 0.41), and overall survival (OS), 27.8 vs 24.3 months (p = 0.68), compared to chemoradiation alone ( Table 1 ). 37 Moreover, the authors reported that 70% of the patients treated with pembrolizumab plus chemoradiation compared to 53% receiving chemoradiation alone underwent surgery. 37 This study is currently enrolling 25 more patients who will receive FOLFIRINOX prior to randomization to CRT± pembrolizumab, which will help to further investigate the immune modulatory effect of chemotherapy followed by CRT.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“… 37 Moreover, the authors reported that 70% of the patients treated with pembrolizumab plus chemoradiation compared to 53% receiving chemoradiation alone underwent surgery. 37 This study is currently enrolling 25 more patients who will receive FOLFIRINOX prior to randomization to CRT± pembrolizumab, which will help to further investigate the immune modulatory effect of chemotherapy followed by CRT. FOLFIRINOX is also used as a neoadjuvant chemotherapy backbone in the NCT03983057 phase 3 trial in patients with locally advanced or borderline resectable PDAC.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%